Evaluation of the service quality management system in transport and logistic companies of the Rostov region ("Journal "U". Economy. Management. Finance.", 2017)
This article examines the main quality of service criteria for transport companies, the quality standards of logistics companies, as well as their actual application in its management. This article analyzes and assesses the quality of services provided at the regional level, whose purpose is to identify weaknesses in the provision of services. At the end of the article, measures were proposed to improve the quality of service in this area.
Keywords: quality of service; transport and logistics companies; quality criteria; quality standard; improvement of service quality